Respostas
respondido por:
0
a)
5.(2x + 1) + 7.(2 + 3x) = = -3 .(x - 3)
10x + 5 + 14 + 21x = - 3x + 9
10x + 21x + 19 = - 3x + 9
31x + 19 = - 3x + 9
31x + 3x = 9 - 19
34x = - 10 (:2)
17x = - 5
x = - 5
17
******************************************
b)
2(x + 1) = 3(2x + 1) - 7(x - 2)
2x + 2 = 6x + 3 - 7x + 14
2x + 2 = 6x - 7x + 3 + 14
2x + 2 = - x + 17
2x + x = 17 - 2
3x = 15
x = 15/3
x = 5
5.(2x + 1) + 7.(2 + 3x) = = -3 .(x - 3)
10x + 5 + 14 + 21x = - 3x + 9
10x + 21x + 19 = - 3x + 9
31x + 19 = - 3x + 9
31x + 3x = 9 - 19
34x = - 10 (:2)
17x = - 5
x = - 5
17
******************************************
b)
2(x + 1) = 3(2x + 1) - 7(x - 2)
2x + 2 = 6x + 3 - 7x + 14
2x + 2 = 6x - 7x + 3 + 14
2x + 2 = - x + 17
2x + x = 17 - 2
3x = 15
x = 15/3
x = 5
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás